PENYULUHAN MENINGKATKAN PENGETAHUAN KEPALA DESA DAN BPD TENTANG MANAJEMEN PENGELOLAAN DAN PENGAWASAN KEUANGAN DESA DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Hadiawan, Agus; Syafarudin, Syafarudin; Dwijono, Amantoto; Warganegara, Arizka; Purba, Darmawan (Prosiding Pengabdian FISIP Unila, 2012)
Extension took place on July 10, 2012 at district hall Natar, South Lampung regency. Participants came from 22 villages in the district Natar. Village heads were 18 people present, who have as a deputy 4 people (sekdes or staff). While BPD was attended by the chairman or members of the BPD. The results and conclusions of this service activities are: (a) counseling given was to increase the knowledge and attitude of the head of the village head and the village of BPD on financial management as set forth in Permendagri 37 of 2007 as well as their efforts to resolve the conflict management and financial control of the village by way of dialogue or deliberation; (b) the level of knowledge of the head of the village head and BPD financial management of the village as provided in Permendagri 37 of 2007 initially low, but after the extension increases the level of their knowledge, (c) the attitude of the village head and BPD attitude that prioritizes dialogue and deliberation to resolve the conflict management and financial control of the village of approval than before held counseling. Keywords: Financial Management of Rural Management, APBDesa